MiR-21 and let-7 cooperation in the regulation of lung cancer - Bai, Jinquan; Shi, Zhenzhou; Wang, Shuting; Pan, Hong; Zhang, Tong (Frontiers in Oncology, 2022)
Background: The occurrence and development of lung cancer is a complex process involving multiple genes, so the therapeutic effect of single gene regulation is poor. We found that the expression of miR-21 in lung cancer tissues and cells was high, while that of let-7 was low, so it is not clear whether their combined regulation will be better than single regulation therapy. The purpose of our study is to verify this situation and the regulatory mechanism between them. Methods: We transfected miRNA mimics or inhibitors into A549 and H460 cells to regulate the levels of miR-21 and let-7 in this two kinds of lung cancer cells. The proliferation, apoptosis, migration and invasion of lung cancer cells were tested. Western blot and qRT-PCR assay were used to verify the results. Their possible regulatory pathways were analyzed by bioinformatics, and the binding sites were verified by luciferase assay. Results: The expression of miR-21 was increased and the let-7 was decreased in lung cancer tissues and cells Compared with paracancerous tissues and normal lung cells（P<0.01）. Down-regulation of miR-21 and up-regulation of let-7 can inhibit tumor cells, and the cooperational regulation is better. Up-regulation of miR-21 and down-regulation of let-7 can promote tumor cells, and the cooperational regulation of tumor-promoting effect is stronger. MiR-21 through wnt/β-catenin pathway and let-7 through PLAG1/GDH1 pathway to regulate the lung cancer cells directly. MiR-21 and let-7 co-participate in the regulation of lung cancer cells through the target gene K-ras. Conclusions: The effect of cooperational regulation of miR-21 and let-7 on lung cancer is more significant than that of single miRNA. MiR-21 and let-7 are important differential genes in lung cancer, which play a role by regulating K-ras gene. So for multi-gene involved lung cancer, the cooperative regulation of two miRNAs will provide new target and direction for lung cancer treatment in future.